Validity and reliability of the Child Perceptions Questionnaires applied in Brazilian children - Gavião Maria; Tureli Maria; Barbosa Taís S (BMC, 2009)
Abstract Background The Child Perceptions Questionnaires (CPQ8-10 and CPQ11-14) are indicators of child oral health-related quality of life. The aim of this study was to assess the validity and reliability of the self-applied CPQ8-10 and CPQ11-14 in Brazilian children, after translations and cultural adaptations in the Brazilian Portuguese language. Methods Schoolchildren were recruited from general populations for pre-testing (n = 80), validity (n = 210), and test-retest reliability (n = 50) studies. They were also examined for dental caries, gingivitis, fluorosis, and malocclusion. Results Children with greater dental caries experience in primary dentition had higher impacts on CPQ domains. Girls had higher scores for CPQ8-10 domains than boys. Mean CPQ11-14 scores were highest for 11-year-old children and lowest for 14-year-old children. Construct validity was supported by significant associations between the CPQ8-10 and CPQ11-14 scores and the global rating of oral health (r = 0.38, r = 0.43) and overall well-being (r = 0.39, r = 0.60), respectively. The Cronbach's alpha was 0.95 for both questionnaires. The test-retest reliabilities of the overall CPQ8-10 and CPQ11-14 scores were both excellent (ICC = 0.96, ICC = 0.92). Conclusion The Brazilian Portuguese version of CPQ8-10 and CPQ11-14 was valuable and reliable for use in the Brazilian child population, although discriminant validity was sporadic due to the fact that impacts are mediated by others factors, such personal, social, and environmental variables.